2005
DOI: 10.1002/chem.200400867
|View full text |Cite
|
Sign up to set email alerts
|

7Li, 31P, and 1H Pulsed Gradient Spin‐Echo (PGSE) Diffusion NMR Spectroscopy and Ion Pairing: On the Temperature Dependence of the Ion Pairing in Li(CPh3), Fluorenyllithium, and Li[N(SiMe3)2] amongst Other Salts

Abstract: 7Li, 31P, and 1H variable-temperature pulsed gradient spin-echo (PGSE) diffusion methods have been used to study ion pairing and aggregation states for a range of lithium salts such as lithium halides, lithium carbanions, and a lithium amide in THF solutions. For trityllithium (2) and fluorenyllithium (9), it is shown that ion pairing is favored at 299 K but the ions are well separated at 155 K. For 2-lithio-1,3-dithiane (13) and lithium hexamethyldisilazane (LiHMDS 16), low-temperature data show that the ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 137 publications
1
27
0
Order By: Relevance
“…3, there is strong ion pairing in THF solution at ambient temperature, based on 7 Li, and 1 H diffusion studies [17]. However, at 155 K, based on the observed D and r H values, the separated ions are favored!…”
Section: Ion Pairingmentioning
confidence: 99%
“…3, there is strong ion pairing in THF solution at ambient temperature, based on 7 Li, and 1 H diffusion studies [17]. However, at 155 K, based on the observed D and r H values, the separated ions are favored!…”
Section: Ion Pairingmentioning
confidence: 99%
“…Values a for the diffusion coefficient, D (·10 À10 m 2 s À1 ), and the hydrodynamic radius, r H (Å ), for the lithium salts in THF [160] Nucleus …”
mentioning
confidence: 99%
“…[7][8][9] Pulsed gradient spin-echo (PGSE) NMR methods have attracted increasing interest, since they allow diffusion coefficients to be measured with high accuracy; they have been successfully used with observation of 7 Li and 31 P nuclei as well as with 1 H NMR. 10,11 We report here the direct measurement of diffusion coefficients to observe ion-association interactions by counter cations with a highly-charged supramolecular assembly.Raymond and coworkers have described the design and chemistry of a class of metal-ligand supramolecular assemblies over the past decade.12-15 The [Ga 4 L 6 ] 12-(L = 1,5-bis(2,3-dihydroxybenzamido)naphthalene) (1) (Figure 1) assembly has garnered the most attention, with the exploration of the dynamics and mechanism of guest exchange as well as the ability of 1 to achieve either stoichiometric or catalytic reactions inside its interior cavity. [16][17][18][19] Recent studies have revealed the importance of counter cations in solution on the chemistry of 1.…”
mentioning
confidence: 99%
“…[7][8][9] Pulsed gradient spin-echo (PGSE) NMR methods have attracted increasing interest, since they allow diffusion coefficients to be measured with high accuracy; they have been successfully used with observation of 7 Li and 31 P nuclei as well as with 1 H NMR. 10,11 We report here the direct measurement of diffusion coefficients to observe ion-association interactions by counter cations with a highly-charged supramolecular assembly.…”
mentioning
confidence: 99%
See 1 more Smart Citation